Strategic role of supply chain intelligence to business performance - Jaharuddin, Nor Siah (WorldConferences.net, 2014)
Competitiveness in business environment nowadays influenced greatly how business organizations strive for business success. The emergence of competitive intelligence (CI) and supply chain management (SCM) in dealing with such circumstances has brought the need to study further on supply chain intelligence. This study examines the impact of SCI on business performance by constructing the components of SCI; and its usage by businesses for competitive advantage to improve their performance. Emphasizing on human potential in managing intelligence, this paper provides the general idea on SCI concept, its link to CI and SCM, and its importance to be subsequently adopted by business organizations as one of the measures in dealing with increasing competitive business environment.